Dawsonite as a Temporary but Effective Sink for Geological Carbon Storage. (September 2022) - Lu, Peng; Zhang, Guanru; Huang, Yi; Apps, John; Zhu, Chen
ABSTRACT: The possibility of using dawsonite mineral trapping as a carbon capture and storage (CCS) strategy intrigues many. In this study, we used a dawsonite-rich (∼10%) CO2 gas reservoir in the Hailar basin in northern China as a natural analogue of a CO2 storage site, along with numerical modeling, to demonstrate that a large amount of dawsonite can be generated in sandstone formations, provided sufficient Na-rich feldspar and CO2 gas are available. While precipitated dawsonite can be preserved only in a hydrodynamically-closed system in the long term under high CO2 fugacity and log((Na + )/(H + )) activities in solution, short-term trapping of CO2 in dawsonite (on the order of 10 kyr) is possible and lowers CO2 pressure, which mitigates the risk of CO2 leakage to the ground surface or overlying drinking water aquifers. The re-dissolution of dawsonite after a few thousand years facilitates progressive dissipation of the gas phase CO2 over time. Consideration of reservoirs or saline aquifers with minerals or formation water that can provide a high abundance of dissolved sodium, significantly increases the number of potential CCS sites globally. Furthermore, alternating water-and-gas injection regimens could enhance the precipitation of dawsonite in Na-rich aquifers. Future editions of the Carbon Storage Atlas should consider aquifer geochemistry in the site selection for secure long-term carbon storage in addition to the volumetric considerations for short-term operation.